ASSESSING ZOONOTIC POTENTIAL: A STUDY ON COMMUNITY ACCESS TO NATURAL RESOURCES IN SEBANGAU NATIONAL PARK, INDONESIA - Panda, Adventus; Priyowidodo, Dwi; Artama, Wayan Tunas; Djohan, Tjut Sugandawaty (Indonesian Journal of Forestry Research, 2025)
The community surrounding Sebangau National Park (SNP) play a key role in comprehending the epidemiological triad. Peat forests have experienced illegal logging and concessions practises from the early 1970s to 2005. The disturbed forest habitat offers the perfect setting for the inter-species transmission of pathogenic agents. The purpose of this study was to identify any possible zoonotic concerns based on the typical community activities across SNP. Community access data were collected using questionnaires and interview in Kereng Bangkirai (Sebangau River), Asem Kumbang, Baun Bango, Tumbang Ronen, Jahanjang, and Karuing (Katingan River) as the representatives’ villages. These settlements are close to the locations used for field sampling (n:102 individuals). The prediction model was developed using CART®Classification for categorical data using MINITAB v. 20.3. We discovered that the model categorised five out of seven factors as important factors. The number of days spent becomes the most crucial predictor (100%), followed by access (95.3%), mode of stay (42.1%), followed by activities (16.8%) and defecation (8.3%), respectively. It was concluded that the longer and deeper they accessed the natural resources; the higher the zoonotic potential would be. The Indonesian Government has established a wildlife health information system, referred to as SehatSatLi, which is designed to protect wildlife genetic resources and reduce the likelihood of zoonotic diseases emerging. It is recommended that stakeholders at all level engaged in coordination, collaboration, and communication as a preventive strategy to inhibit the possible transmission of zoonotic diseases between wildlife and humans, vice versa.